Are Digital Menus Really Better than Traditional Menus? The Mediating Role of Consumption Visions and Menu Enjoyment. Issue 1 (May 2020) - Yim, Mark Yi-Cheon; Yoo, Chan Yun
This study examined consumers' responses to interactive media in a restaurant setting (i.e., digital menus). Study 1 tested a conceptual model, which examined the underlying process shaping customers' evaluations of a Web-based digital menu. The results demonstrated that consumption visions and menu enjoyment mediated the effects of perceived interactivity on attitudes toward the digital menus. Study 1 also identified direct product experience as an important moderator of the relationship. Study 2 extended and replicated Study 1 in an offline setting by conducting a lab experiment that compared the use of digital and traditional menus in ordering foods that participants have experienced versus those they have not. In general, tablet-based digital menus generated greater enjoyment, increased intentions to adopt, and encouraged participants to order more within a shorter time. But they were preferred only for less-experienced foods. Furthermore, consumption visions were important mediators of interactivity effects in the digital menu condition, but not in the traditional paper menu condition, while menu enjoyment played a mediating role in both conditions.